Notes on the genus Echinoaesalus Zelenka, 1993 (Coleoptera: Lucanidae), with the description of a new species from the Malay Peninsula - Huang, Hao; Bartolozzi, Luca; Chen, Chang-Chin (Zootaxa, 2015)
Echinoaesalus cechovskyi new species is described from the Malay Peninsula. Echinoaesalus hidakai borneoensis Huang & Imura, 2011 is elevated to the species level as E. borneoensis new status. The male or female genitalia of Echinoaesalus timidus (Krikken, 1975), E. hidakai (Araya, Kon, & Johki, 1993), E. borneoensis, and E. sabahensis Zelenka, 1994 are described and illustrated for the first time. The intraspecific variation of E. timidus is discussed.